2021
DOI: 10.1021/acsnano.1c04514
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Extracellular Vesicles Restore the Impaired Cellular Uptake and Attenuate Intervertebral Disc Degeneration

Abstract: Extracellular vesicles (EVs) are potential alternatives for mesenchymal stem cells (MSCs) in the treatment of musculoskeletal degenerative diseases, including intervertebral disc degeneration (IDD). Usually, EVs are internalized and then deliver bioactive molecules that impart phenotypic changes in recipient cells. For effective utilization of EVs in the IDD therapy, understanding the mechanism of EV uptake is of vital importance. In this study, we found that EVs delivered antioxidant proteins to protect again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 55 publications
0
66
0
Order By: Relevance
“…In recent studies, caveolae associated protein 2 (Cavin-2) modified engineered extracellular vesicles were used to treat disc degeneration. Cavin-2 modification significantly increased the extracellular vesicle uptake efficacy in degenerating NP cells compared to stem cell-derived extracellular vesicles alone [135]. Collectively, these studies demonstrate the great potential of bioactive materials in targeting IVD ECM degeneration, but more studies are needed to evaluate their long-term safety and efficacy (Table 1).…”
Section: Biomaterialsmentioning
confidence: 84%
“…In recent studies, caveolae associated protein 2 (Cavin-2) modified engineered extracellular vesicles were used to treat disc degeneration. Cavin-2 modification significantly increased the extracellular vesicle uptake efficacy in degenerating NP cells compared to stem cell-derived extracellular vesicles alone [135]. Collectively, these studies demonstrate the great potential of bioactive materials in targeting IVD ECM degeneration, but more studies are needed to evaluate their long-term safety and efficacy (Table 1).…”
Section: Biomaterialsmentioning
confidence: 84%
“…The stained sections were then observed under a microscope; the number of cells and the structure of NP tissue were observed to evaluate the severity of IVDD. The degenerative degree of discs was evaluated by a histological grading scale [ 27 29 ]. The scale was based on five categories of disc changes: with 0 points for a normal disc and 15 points for a severely degenerated disc.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that injectable hydrogels can be used to load antioxidant drugs to regulate oxidative stress. [82][83][84][85][86] The antioxidants commonly used in the treatment of AMI include vitamins, [87,88] polyphenols, [89,90] and mitochondriatargeted drugs. [91] The therapeutic effect of vitamins has been studied and some advances have been reported in animal AMI models.…”
Section: Injectable Hydrogels For Antioxidation Therapy Of Amimentioning
confidence: 99%